2019
DOI: 10.4274/tjps.58966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Lipid Peroxidation Product 4-Hydroxynonenal on Neuroinflammation in Microglial Cells: Protective Role of Quercetin and Monochloropivaloylquercetin

Abstract: Objectives:The lipid peroxidation-derived aldehyde 4-hydroxynonenal (HNE) has been implicated in a number of oxidative stress-induced inflammatory pathologies such as neurodegenerative diseases and aging. In this regard, we investigated the effects of HNE on neuroinflammatory responses by measuring cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS) induction with cytokine production. In addition, we measured nuclear factor erythroid 2-related factor 2 (Nrf-2)/Kelch-like ECH-associated protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The low bioavailability often led to the use of high QUE doses to achieve measurable outcomes. Different QUE formulations were developed to increase bioavailability following PO administration 66,67 . Many different strategies were tested, such as nanoparticle‐based and by immersion in oil 12,37,38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low bioavailability often led to the use of high QUE doses to achieve measurable outcomes. Different QUE formulations were developed to increase bioavailability following PO administration 66,67 . Many different strategies were tested, such as nanoparticle‐based and by immersion in oil 12,37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Different QUE formulations were developed to increase bioavailability following PO administration. 66,67 Many different strategies were tested, such as nanoparticle-based and by immersion in oil. 12,37,38 In QUE-loaded nanoparticles, QUE molecules are encapsulated into lipidic nanocarriers, increasing permeability across biological barriers, bioavailability and efficacy of QUE nanocrystals exceeded those of free QUE.…”
Section: Strategies To Improve Que Bioavailabilitymentioning
confidence: 99%
“…Deltamethrin exposure significantly increased protein levels of 4-HNE in MMCs, and was correlated with the production of ROS and inflammatory cytokines. Several studies have shown that 4-HNE acts as a critical signaling molecule that triggers inflammatory responses after the induction of oxidative stress in microglia and astrocytes [ 73 , 74 , 75 ]. These results suggest that an imbalance in antioxidant homeostasis and oxidative stress triggers an inflammatory response through ER stress pathways, following exposure to deltamethrin.…”
Section: Discussionmentioning
confidence: 99%